2017
DOI: 10.1523/eneuro.0049-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Detection of Odorant Functional Groups byDrosophila melanogaster

Abstract: A remarkable feature of olfaction, and perhaps the hardest one to explain by shape-based molecular recognition, is the ability to detect the presence of functional groups in odorants, irrespective of molecular context. We previously showed that Drosophila trained to avoid deuterated odorants could respond to a molecule bearing a nitrile group, which shares the vibrational stretch frequency with the CD bond. Here, we reproduce and extend this finding by showing analogous olfactory responses of Drosophila to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
0
11
0
3
Order By: Relevance
“…electron transfer from a donor via an odorant to an acceptor, enabled by excita4on of molecular vibra4ons in the odorant 1 . The physics behind this idea was shown to be sound [2][3][4][5][6] , and strong behavioural and perceptual evidence in its favour has come from experiments on insects and humans [7][8][9][10] . However, the idea currently remains controversial [11][12][13] , in part because vertebrate olfactory receptors are members of the G-protein-coupled receptor (GPCR) family: GPCRs are thought to work by a conven4onal lock and key mechanism 14,15 .…”
Section: Introduc4onmentioning
confidence: 99%
“…electron transfer from a donor via an odorant to an acceptor, enabled by excita4on of molecular vibra4ons in the odorant 1 . The physics behind this idea was shown to be sound [2][3][4][5][6] , and strong behavioural and perceptual evidence in its favour has come from experiments on insects and humans [7][8][9][10] . However, the idea currently remains controversial [11][12][13] , in part because vertebrate olfactory receptors are members of the G-protein-coupled receptor (GPCR) family: GPCRs are thought to work by a conven4onal lock and key mechanism 14,15 .…”
Section: Introduc4onmentioning
confidence: 99%
“…1 Traditional views on the topic 2 have been challenged by recent findings, [3][4][5] but conclusive evidence could not be provided yet, leaving the debate widely open. [6][7][8][9] Odour perception initiates on the membrane of olfactory receptor neurons, where volatile odorants interact with olfactory receptor proteins triggering a signalling cascade.…”
Section: Introductionmentioning
confidence: 99%
“…Recent electrophysiology experiments in Drosophila traced back differential responses to isotopomers to the odour receptor neurons of the antennae. 3,5 However, a recent imaging experiment in Drosophila showed that an observed differential response to benzaldehyde in one olfactory receptor could be fully explained by a minute impurity of 6 ppm within the odour sample. 29 Such impurity, undetectable by gas chromatography, had overshadowed the response to the nominal odorant.…”
Section: Introductionmentioning
confidence: 99%
“…Αυτό το αποτέλεσμα υποδεικνύει ότι οι μύγες ανταποκρίνονται ανεξάρτητα στους διαφορετικούς τρόπους δόνησης ενός μορίου και υπονοεί την πιθανή εμπλοκή πολλαπλών οσφρητικών υποδοχέων και όχι μόνο ενός, στην ανίχνευση της δόνησης. Ωστόσο, είναι δύσκολο να εκτιμηθεί η ακριβής έκταση και ευαισθησία της ανίχνευσης αυτής από την Δροσόφιλα σε όρους συχνότητας και έντασης[116]. Λειτουργικές ομάδες με παρόμοιες συχνότητες δόνησης πρέπει να έχουν παρόμοιες οσμές.2.…”
unclassified
“…Άρα η υπόθεση αυτή υστερεί και δεν μπορεί να υποστηριχθεί. Να σημειωθεί εδώ ότι η μεταβολή του τόπου ενεργοποίησης των υποδοχέων είναι εντελώς αδύνατη προς το παρόν και αυτό γιατί δεν είναι καν γνωστό σε ποιο ακριβώς σημείο προσδένεται το οσμογόνο μόριο[116].Στη θεωρία των δονήσεων, η οσμή ενός μορίου είναι κωδικοποιημένη στη μοριακή δόνηση του ίδιου του μορίου. Ο μεγάλος αριθμός των οσφρητικών υποδοχέων άλλωστε υποδεικνύει ότι πρέπει ανά πάσα στιγμή να υπάρχουν αρκετοί υποδοχείς τους οποίους θα πλησιάσει ένα οποιοδήποτε μόριο έτσι ώστε όλες οι κορυφές του φάσματός του να αναγνωριστούν.…”
unclassified